Correlation between Blood Pressure and vascular complications after coronary artery angiography - Golnoosh Benvan; Mitra SedghiSabet; Mojgan Baghaei; Zahra Atrkar-e Roshan; Asieh Sedighi (Guilan University of Medical Sciences, 2016)
Introduction: Post-coronary angiography vascular complications (PCAVC) may cause serious life threats, thus recognition of related factorse is needed to prevente complication Objective: This study was conducted to determine correlation between hypertension and vascular complications after coronary artery angiograph among hospitalized patients therapeutic- educational center in Rasht Methods: This descriptive analytical correlational study was performed on 400 patients admitted in angiography wards at Dr Heshmat therapeutic- educational centers by sequential sampling method in 2013. Data were gathered by a 3-part tool including; demographic information questionnaire, blood pressure recording forms and PCAVC occurance (Hematoma, ecchymosis and bleeding) during 24h after angiography until heet removal through interview and observation methods. Data were analyzed by using descriptive and analytic (X2, independent T and ANOVA) statistics tests Results: Majority of samples (56.2%) had history of Hypertension. Mean of pre-angiographic systolic and diastolic blood pressure were 129.46±21.63 and 76.85± 1.15 and pre-sheat extraction were 132.96±18.02 and 78.85±1.02mmHg. Vascular complications were observed in 24 percents of samples that majority of them were ecchymosis (71.4%). A significant relationship was seen between history of HTN and overall PCAVC (p<0.005), ecchymosis (p<0.006) and hematoma (p<0.046). The statistical tests showed a significant relation between mean of systolic BP before sheet removal with overall PCAVC (p<0/003) and ecchymosis (p<0.004) and diastolic BP with overall PCAVC (p<0.0006), ecchymosis (p<0.0009) Conclusion: Screen of high occurance of PCAVC among patients after angiography with history of hypertension and systolic and diastolic BP before sheet removal is required to diagnose high risk patients who need special and highy quality of care